A framework for cybersecurity strategy for developing countries: case study of Afghanistan - Salamzada, Khosraw; Zarina Shukur,; Marini Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2015)

(untitled)
Given the importance of cyber space for country development, many countries have invested large amount of money for cyber space application. Since, based on official documents, Afghanistan is in the process of integrating ICT into its critical information infrastructure, to this end, the country may face various challenges including cyber security. Due to various potential threats and risks to Afghanistan cyber security, a comprehensive cyber security strategy is necessary. Accordingly, Afghanistan has introduced an ICT security law. However, nowadays day by day internet is involving great portion of government and non-government sections. The country must introduce a comprehensive and appropriate cyber security strategy to tackle all of the issues and risks related to this arena. The aim of this study is to propose cyber security strategy based on developed countries experiences in cyber security, specifically Malaysia, because Malaysia and Afghanistan are both Islamic countries with cultural and religious values. Furthermore, Malaysia is considered as a developed country in terms of cyber security. Therefore, in this study, based on literature review and official documents, the current status of ICT as well as cyber threats were identified in Afghanistan context. In addition, to evaluate the current status of cyber security strategy in Afghanistan and Malaysia, some experts were interviewed and accordingly based on their suggestions and Malaysian experience in cyber security, a strategy framework was proposed for Afghanistan to address the ever-growing cyber threats. Then, the proposed cyber security strategy framework was evaluated by interviewing three experts in the field.